Reutilización de información pública y protección de datos personales - TRONCOSO RAIGADA, Antonio (Revista General de Información y Documentación, 2009)
The article analyzes the constitutional basis of the reuse of the public information connecting it mainly to the boost of the market economy and to a lesser extent to the openness. Secondly it analyzes the personal data protection as a limit to the reuse of the public information, establishing that this cannot imply a cession of the personal data without consent –since there is no legal authorization- and nowadays the only possible way is to dissociate the information or to use of the accessible sources to the public.
Keywords: Reuse of public information; Openness and personal data protection